Location Quotient Analysis in Determining Cattle Base in Aceh, Indonesia - Mastuti, Rini; Fironika, Mauliza; Jamil, Muhammad; Hanisah (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Aceh province is an area that has prospects for the development of cattle. The potential of the Province of Aceh has considerable prospects for improving its economy in the future. This study uses a quantitative descriptive approach using a survey method based on secondary data. The data was taken from related government agencies, such as the Aceh Provincial Animal Husbandry Service, and the Aceh Statistics Centre. This study aims to identify the livestock base in various districts/cities in Aceh Province. The secondary data obtained was used as the basis for the survey method used in this study. This study used a quantitative descriptive research design and conducted a Location Quotient (LQ) analysis to identify the location of cattle centres in Aceh Province. The livestock population in Aceh Province in 2012-2021 is used as data in this study. The results of the study found 13 livestock base areas in Aceh Province namely Aceh Tamiang, Aceh Singkil, Nagan Raya, East Aceh, Pidie Jaya, Bireuen, Aceh Besar, Simeulue, Southeast Aceh, Banda Aceh City, Aceh Jaya, Pidie, and Gayo Luwes.